NORMATIVE DIMENSIONS OF SPEECH ACTS: EXPLORATORY STUDY IN SASAK SPEECH COMMUNITY - Muh. Junaidi (MABASAN, 2018)
This study investigates normative dimensions of speech acts. It analyzes the nature of normative dimension of speech acts.To get empirical data, 9 participants were chosen as sources of spoken language data: 2 tuan guru giving speeches in formal contexts; and 7 people engaging in casual conversations in informal context. To collect data, observation and voice recording was used. Prior to analysis, the data were transcribed, labeled and classified according to categories that appeared from the data. Findings reveal and advocate the normative and moral dimensions of speech acts generated from agent’s change normative standing to hearers in terms of right, obligation and responsibility. As a result, the study argues that moral values embedded in speech act performance such honesty, truth, self-control and respect, obedience and so forth could be taught in order to foster children good character development in comprehensive ways including moral reasoning, affection and behaviors. For that reason, moral values teaching based on speech act normativity and morality could be used as an arena for bearing good character corresponding to the process of acquiring of the first language or learning the second/foreign language. This could be a starting point for teaching moral competence through language institution that are more affordable, accessible and learnable for all rational human being all over the world. Furthermore, those moral values might be the foundation for moral action of children to bear the awareness of good interpersonal or intersubjective relationship. Based on the limitation of the study, it needs to hold further study as to the practical model of teaching moral values on the bases of moral values embedded in performing speech acts.Kajian ini menelaah tentang karakter dimensi normatif tindakan berbahasa. Data empiris diperoleh dengan melibatkan 9 partisipan, yakni 2 tuan guru yang memberikan ceramah dalam konteks formal dan 7 orang yang terlibat percakapan kasual dalam konteks informal. Data dikumpulkan melalui observasi dan rekaman suara. Sebelum analisa, data tersebut ditranskripsi, dilabeli dan diklasifikasikan. Kajian ini mengungkapkan dan mendukung  adanya dimensi normatif dan moral tindakan berbahasa yang dibentuk dari perubahan kedudukan normatif pembicara dan pendengar terkait hak, kewajiban dan tanggungjawab. Kajian ini mendukung bahwa dimensi normatif dan nilai moral yang melekat dalam setiap tindakan berbahasa seperti, kejujuran, kebenaran, komitmen, tanggungjawab, kontrol diri, saling menghargai dan lain-lain yang bisa diajarkan  dalam pengembangan karakter anak yang bermoral dengan cara yang komprehensif meliputi penalaran moral, afeksi dan tindakan. Oleh sebab itulah, pengajaran nilai-nilai moral berbasis moralitas dan normativitas tindakan berbahasa bisa digunakan sebagai arena pendidikan karakter atau nilai. Ini bisa menjadi langkah awal pengajaran kompetensi moral melalui instiusi bahasa. Di samping itu, nilai-nilai moral tersebut merupakan fondasi dalam tindakan anak yang bermoral untuk membangun kesadaran interpersonal anak yang baik. Berdasarkan keterbatasan kajian ini, diperlukan kajian lebih lanjut tentang model praktis pengajaran nilai-nilai moral berbasis dimensi normatif dan moral yang inheren dalam setiap tindakan berbahasa.